Avaliação do presenteísmo em mulheres com e sem dismenorreia - Godoy, Amanda Garcia de (2022)
Objectives: The objective of the present study was to evaluate presenteeism due to dysmenorrhea in adult women. Methods: Our primary endpoints were presenteeism, assessed with the Stanford Presenteeism Scale-6 (SPS-6), and dysmenorrhea-related pain intensity was assessed with the Numerical Pain Scale. Our secondary outcome was absenteeism due to dysmenorrhea in the last three months. The collection was carried out online with adult women. For statistical analysis, the Kolmogorov-Smirnov, Mann-Whitney U, Spearman correlation, chi-square tests and binary logistic regression with backward insertion method were used. A p<0.05 was considered for significance. Results: A total of 408 women were included in the analysis, of which 228 reported menstrual cramps. Of the women who reported dysmenorrhea, 58.3% also reported presenteeism due to the condition (p<0.001). There was a negative correlation between the SPS-6 score and the intensity of pain related to dysmenorrhea. The score of the SPS-6 avoid distraction subdimension showed a moderate negative correlation with the intensity of pain related to dysmenorrhea, and the finish work subdomain showed a weak negative correlation with the same variable. Higher pain intensity and practice of absenteeism in the last three months increase the chances of presenteeism (0.73 and 0.58 times, respectively). We found a moderate negative correlation between the SPS-6 score and absenteeism. Conclusion: The occurrence of presenteeism was higher in women with dysmenorrhea, and presenteeism is higher according to the intensity of perceived pain related to dysmenorrhea. Greater pain intensity related to dysmenorrhea and absenteeism in the last three months increase the chances of presenteeism among women with dysmenorrhea.